Short communication on the role of cellulosic fiber-based packaging in reduction of climate change impacts. (15th February 2021) - Schenker, Urs; Chardot, Julia; Missoum, Karim; Vishtal, Alexey; Bras, Julien
Highlights: Cellulose-based solutions can improve environmental performance of food packaging. Food products require specific barrier functions from cellulose-based packaging. Eco-design enables quantifying environmental performance and identifying trade-offs. Fulfilling the barrier requirements for food product packaging is crucial. Abstract: This short communication describes the climate change impacts of using cellulose, and more precisely cellulosic fiber-based materials, in food packaging, representing current and emerging industrial state of the art technology, without specific reference to current scientific advances. First, the different types of cellulosic fiber-based packaging materials, which can be used to replace fossil-based packaging materials, are presented for flexible and rigid applications. The focus is on technological solutions with packaging properties that enable the protection of commonly sold food products. The manufacturing processes associated with these cellulosic fiber-based materials is described and the environmental impact assessment of 4 selected case studies presented: stand-up pouches, flexible flow wraps, frozen or chilled food trays, and molded pulp lids. A simplified eco-design Life Cycle Assessment (LCA) was then performed to compare each solution with its fossil-based counterpart. Differences and similarities between the various cellulosic solutions have been identified. Furthermore, the assessment confirms that cellulosic fiber-based materials have reduced environmental impacts as compared to fossil-based counterparts, if a similar packaging weight is obtained. Indeed, all impacts of plastics are between 3 and 5 kg CO2 eq/kg, while all impacts of cellulosic fiber-based materials are below 1.5 kg CO2 eq/kg.